Using Experiential Learning and OSCEs to Teach and Assess Tobacco Dependence Education with First‐Year Dental Students. Issue 5 (1st May 2014) - Romito, Laura; Schrader, Stuart; Zahl, David
Abstract : Previous research has indicated that dentists do not routinely engage in tobacco cessation interventions with their patients due, in part, to a lack of training in the predoctoral curriculum. From 2010 to 2012, this study at one U.S. dental school evaluated the effectiveness of experiential learning and objective structured clinical examinations (OSCEs) to improve first‐year dental students' knowledge and beliefs about tobacco dependence and cessation interventions. Analysis indicated acceptable reliability and student performance for the OSCE. In all three years, there were statistically significant increases in student knowledge (p<0.001). In each year, there were also statistically significant shifts in student perceptions of preparedness (p<0.001 to p=0.034) and willingness (p<0.001 to p=0.005) to provide tobacco dependence treatment to patients. Results suggest that OSCEs utilizing standardized patients may be an effective method for assessing tobacco dependence education. Preparing for and participating in an OSCE with a standardized patient may help increase student knowledge and shape the beliefs of early dental students about engaging in patient tobacco cessation interventions. Findings were mixed on the impact of experiential learning on OSCE performance, suggesting further research is needed.